2014
DOI: 10.1371/journal.pone.0094097
|View full text |Cite
|
Sign up to set email alerts
|

Attempted Suicide in Bipolar Disorder: Risk Factors in a Cohort of 6086 Patients

Abstract: ObjectiveBipolar disorder is associated with high risk of self-harm and suicide. We wanted to investigate risk factors for attempted suicide in bipolar patients.MethodThis was a cohort study of 6086 bipolar patients (60% women) registered in the Swedish National Quality Register for Bipolar Disorder 2004–2011 and followed-up annually 2005–2012. Logistic regression was used to calculate adjusted odds ratios for fatal or non-fatal attempted suicide during follow-up.ResultsRecent affective episodes predicted atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
75
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 30 publications
4
75
2
2
Order By: Relevance
“…Strong evidence supports the impact of any type of abuse (physical, emotional, sexual, or neglect), particularly at younger ages, with the emergence of mental illness [31] . The presence of current stressors was not found to be associated with HSA, in contrast to a study [13] which proposed significant effects of multiple social factors on suicide attempts in women. However, our HSA data obtained at intake was historical, while the stressor measure was compiled from each subsequent session.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Strong evidence supports the impact of any type of abuse (physical, emotional, sexual, or neglect), particularly at younger ages, with the emergence of mental illness [31] . The presence of current stressors was not found to be associated with HSA, in contrast to a study [13] which proposed significant effects of multiple social factors on suicide attempts in women. However, our HSA data obtained at intake was historical, while the stressor measure was compiled from each subsequent session.…”
Section: Discussioncontrasting
confidence: 99%
“…Several authors reported an association between substance abuse and suicide attempts in patients with BD [12,13] , specifically alcohol overuse [14] , but Cassidy [6] did not find a similar correlation. An anxiety diagnosis comorbid with BD was associated with increased HSA in some studies [14,15] but not in others [16] .…”
mentioning
confidence: 97%
“…Existing evidence indicates that fewer suicides are attempted during manic episodes. 31 Therefore, motor impulsivity does not appear to be associated with SA as a trait or state characteristic. Moreover, according to a recent review of impulsivity and suicidality in BD, SAs in patients with higher motor impulsivity tend to be less lethal.…”
Section: Discussionmentioning
confidence: 95%
“…8,[46][47][48] With respect to treatment, although antipsychotics and mood stabilizers seem to improve global functioning in patients with borderline and/or schizotypal PD, 49 few studies have addressed concurrent medical and psychological treatment in bipolar patients with comorbid PD. In this context, lamotrigine and valproate may alleviate symptoms of both BD and borderline PD, 50 and psychoeducation seems useful as an adjunctive treatment in the prophylaxis of BD with any comorbid PD.…”
Section: Discussionmentioning
confidence: 99%